2021
DOI: 10.1080/87565641.2020.1858421
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cognitive Functions and Academic Skills in 9- to 10-year-old Children with Borderline Intellectual Functioning

Abstract: This longitudinal study examined whether the cognitive and academic development of children (M age = 10.52 years) with Borderline Intellectual Functioning (BIF), is characterized by developmental delay or atypical development. Cognitive tasks, arithmetic tasks, and reading tasks were administrated during three succeeding years to the BIF group and a Chronological Age-Matched Comparison (CAMC) group. The BIF children displayed weaknesses in relation to all tasks, and slower developmental rates on four arithmeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…ability [4]. Poor academic performance [4][5][6][7] including difficulties with reading and arithmetic [8,9] due to weak executive functions, and short-term and working memory [10], communication problems, and social problems [7] also accompany it. A recent prospective study of children and adolescents with borderline intelligence reported developmental delays in language and motor development and, at school age, difficulties with executive functioning, reading, and arithmetic.…”
Section: Introductionmentioning
confidence: 99%
“…ability [4]. Poor academic performance [4][5][6][7] including difficulties with reading and arithmetic [8,9] due to weak executive functions, and short-term and working memory [10], communication problems, and social problems [7] also accompany it. A recent prospective study of children and adolescents with borderline intelligence reported developmental delays in language and motor development and, at school age, difficulties with executive functioning, reading, and arithmetic.…”
Section: Introductionmentioning
confidence: 99%